Peranan Informasi Kos dalam Keputusan Manajemen dan Perubahan Lingkungan Manufaktur di Indonesia - Yunianto, Andan (Journal of Accounting and Investment, 2001)
In theory, the use of management information for business decision boarding. Management decisions include decisions on new product launches, product selling prices, make or buy a product, and product retirement. in this regard, this study aims to determine the extent to which management uses boarding information products in support of its decision. Information about boarding role in decision-making are important information in the development of appropriate methods to calculate kos product. The method can be used is the conventional method and the method of Activity-Based Costing (ABC). The use of a calculation method kos product is inseparable from the corporate environment. Therefore, the second and third goals of this study was to determine the extent to which the changes occurred in the Indonesian manufacturing environment and the calculation method boarding what products are in accordance with the conditions of the manufacturing environment. This study uses primary data collected through questionnaires in early 1999. The questionnaire was sent to the finance manager of a manufacturing company that is contained in the book Top Companies Big Groups in Indonesia 6th edition 1996-1997 published by PT Kompass. Of the amount of existing manufacturing companies taken at random sample of 250 companies as respondents and only 60 can be used as a sample for further processing as a basis for analysis. Data analysis is done by comparing visually without statistical test through to the number of respondents were grouped into three categories of answers.